Regulation of alternative splicing in human obesity loci. Issue 10 (12th August 2016) - Kaminska, Dorota; Käkelä, Pirjo; Nikkola, Elina; Venesmaa, Sari; Ilves, Imre; Herzig, Karl‐Heinz; Kolehmainen, Marjukka; Karhunen, Leila; Kuusisto, Johanna; Gylling, Helena; Pajukanta, Päivi; Laakso, Markku; et al.
Abstract : Objective: Multiple obesity susceptibility loci have been identified by genome‐wide association studies, yet the mechanisms by which these loci influence obesity remain unclear. Alternative splicing could contribute to obesity by regulating the transcriptomic and proteomic diversity of genes in these loci. Methods: Based on a database search, 72 of the 136 genes at the 13 obesity loci encoded multiple protein isoforms. Thus, alternative splicing of these genes in adipose tissue samples was analyzed from the Metabolic Syndrome in Men population‐based study and from two weight loss intervention studies (surgical and very low calorie diet). Results: Alternative splicing was confirmed in 11 genes with PCR capillary electrophoresis in human subcutaneous adipose tissue. Interestingly, differential splicing of TRA2B, BAG6, and MSH5 was observed between lean individuals with normoglycemia and overweight individuals with type 2 diabetes. Of these genes, we detected fat depot‐dependent splicing of TRA2B and BAG6 and weight loss‐induced regulation of MSH5 splicing in the intervention studies. Finally, body mass index was a major determinant of TRA2B, BAG6, and MSH5 splicing in the combined data. Conclusions: This study provides evidence for alternative splicing in obesity loci, suggesting that alternative splicing at least in part mediates the obesity‐associated risk in these loci.